Grundlegende Aspekte des 2K-Metallpulverspritzgießens - Hage, Christoph (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2013)
An important requirement for the combination of two materials in order to get a low stress and low warpage, crack-free composite component is a timely synchronized sintering behavior of both components. The aim of this work was to analyze the effect of the particle size distribution on the sintering behavior and the resulting consequences of the particle size change for the flow properties during injection molding.